2013
DOI: 10.1111/mmi.12155
|View full text |Cite
|
Sign up to set email alerts
|

Inositol 1,4,5‐trisphosphate receptor regulates replication, differentiation, infectivity and virulence of the parasitic protist Trypanosoma cruzi

Abstract: SummaryIn animals, inositol 1,4,5-trisphosphate receptors (IP3Rs) are ion channels that play a pivotal role in many biological processes by mediating Ca 2+ release from the endoplasmic reticulum. Here, we report the identification and characterization of a novel IP3R in the parasitic protist, Trypanosoma cruzi, the pathogen responsible for Chagas disease. DT40 cells lacking endogenous IP3R genes expressing T. cruzi IP3R (TcIP3R) exhibited IP3-mediated Ca 2+ release from the ER, and demonstrated receptor bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
92
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(97 citation statements)
references
References 64 publications
4
92
0
1
Order By: Relevance
“…Whenever analyses were not restricted to overall nucleotide similarity, similar CRCs could be detected also in some other protozoan species. In the flagellated protozoans, Trypanosoma brucei [135] and Trypanosoma cruzi [136], IP 3 R channels have thus been identified, complemented by thorough experimental work comparable to that with Paramecium. This included activation studies, intracellular localisation, knockdown experiments and functional analysis.…”
Section: Mixed Types Of Crcs and Common Originmentioning
confidence: 97%
“…Whenever analyses were not restricted to overall nucleotide similarity, similar CRCs could be detected also in some other protozoan species. In the flagellated protozoans, Trypanosoma brucei [135] and Trypanosoma cruzi [136], IP 3 R channels have thus been identified, complemented by thorough experimental work comparable to that with Paramecium. This included activation studies, intracellular localisation, knockdown experiments and functional analysis.…”
Section: Mixed Types Of Crcs and Common Originmentioning
confidence: 97%
“…Only very recently has an InsP 3 R been cloned in full and analysed in functional tests within the pathogenic flagellates Trypanosoma brucei (Huang et al, 2013) and Trypanosoma cruzi (Hashimoto et al, 2013); however, the precise domain structure remains to be shown. For other protozoa, no data are available that are comparable with those of the P. tetraurelia CRC types CRC-II and CRC-IV (those that have been analysed most thoroughly) -although CRCs related to CRC-II, which serves for the release of Ca 2+ , must be ubiquitously present in all related organisms according to physiological data ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Characterized by domain and functional analysis Ladenburger and Plattner, 2011); see text for details. Plattner et al, 2012. f For recent analysis see Huang et al, 2013. g For recent analysis see Hashimoto et al, 2013. local increases in [Ca 2+ ] i by approximately two orders of magnitude. These localised changes in [Ca 2+ ] i regulate numerous different functions, from secretion (exocytosis), locomotion (including ciliary beat regulation) to cell division (Berridge et al, 2000;Clapham, 2007).…”
Section: Prokaryotic Foundation Of Camentioning
confidence: 99%
“…The channel is localized to the inner mitochondrial membrane of a variety of cells, including Trypanosoma brucei (10). TcIP 3 R was reported to have ER localization in T. cruzi (11). However, the immunofluorescence evidence reported was disputed (12), because there was no clear reticular pattern or co-localization with a T. brucei ER marker, TbBiP, in the figures published (11).…”
mentioning
confidence: 99%
“…TcIP 3 R was reported to have ER localization in T. cruzi (11). However, the immunofluorescence evidence reported was disputed (12), because there was no clear reticular pattern or co-localization with a T. brucei ER marker, TbBiP, in the figures published (11). In addition, the T. brucei IP 3 R localized to the acidocalcisomes as demonstrated using antibodies against the endogenous tagged protein (13) and specific antibodies against the protein (14), as well as proteomic and functional analyses (13,14).…”
mentioning
confidence: 99%